PKM Pemberdayaan Ibu-Ibu Majelis Ta’lim Ulil Albab Melalui Pelatihan Make Up Pesta Tanpa Pencabutan Bulu Alis di Kelurahan Parangtambung Kota Makassar - Rika Riwayani; Izmi Burhanuddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract - Empowerment training for ta'lim assembly ladies through party make-up training without eyebrow hair removal in Parangtambung sub-district, Makassar City is a community partnership program (PKM) as a solution to the problem of less productive housewives in Parangtambung village Makassar City. The target audience for this training is 15 housewives in Parangtambung village Makassar City. The training method is carried out in the form of lectures, questions and answers, discussions and practice. This PKM program aims to: 1) become more skilled in the world of cosmetology. 2) develop the potential that has been owned for its own and commercial purposes independently. 3) increase productivity with makeup activities which of course can function for beauty and health. After conducting training through PKM research activities, Empowering housewives through make up training in ParangTambung Village, Makassar City, it can be concluded that: A total of 15 training participants have understood and understood well how to carry out makeup directly both for themselves and others. Furthermore, as many as 15 training participants were not only skilled in makeup but also inspired the importance of empowering housewives through ongoing makeup training.Keywords: Training, Make Up, Housewife